Conception and evaluation of a comprehensive patient empowering and pervasive healthcare system - Marco Johns (2013)
Pervasive Healthcare is a novel eld which uses computer systems for the improvement of healthcare. Patient Empowerment aims to enable and encourage an individual to take a more active role in his own healthcare. In this thesis these two concepts are combined, utilizing technologies such as Personal Health Records and Information Collection in order to empower the user. For this purpose a broadly aimed requirement analysis has been conducted and based on these requirements an architectural system concept has been drafted. Finally this concept has been brie y evaluated qualitatively and based on the previously derived architectural requirements.
Keywords: Pervasive healthcare; Patient empowerment; System conception